Exercise training, energy metabolism, and heart failure - Ventura-Clapier, R. (Applied Physiology, Nutrition, and Metabolism, 2009)
Energy metabolism is at the crossroad of cell function and dysfunction. Cardiac and skeletal muscle cells, the energy metabolism of which is high, fluctuating, and adaptable to the special needs of the body, have developed sophisticated strategies for synthesizing, transferring, and utilizing energy in accordance with the needs of the body. Adaptation to endurance training mainly involves energetic remodelling in skeletal muscles, but less is known for the cardiac muscle. Alterations in energy metabolism participate in many pathophysiological processes, among which is heart failure. Because endurance training improves symptoms and quality of life and decreases mortality rate and hospitalization, it is increasingly recognized as a beneficial practice for heart failure patients. The mechanisms involved in the beneficial effects of exercise training are far from being understood. Proper evaluation of these mechanisms is thus a major health issue for populations living in industrialized countries. This review mainly focuses on oxidative metabolism and intracellular energy transfer in muscles and the heart, their alterations in heart failure, and the effects of endurance exercise training.